2014
DOI: 10.1002/acn3.39
|View full text |Cite
|
Sign up to set email alerts
|

GRIN2A mutation and early‐onset epileptic encephalopathy: personalized therapy with memantine

Abstract: Objective Early-onset epileptic encephalopathies have been associated with de novo mutations of numerous ion channel genes. We employed techniques of modern translational medicine to identify a disease-causing mutation, analyze its altered behavior, and screen for therapeutic compounds to treat the proband. Methods Three modern translational medicine tools were utilized: 1) high-throughput sequencing technology to identify a novel de novo mutation; 2) in vitro expression and electrophysiology assays to confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
207
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(213 citation statements)
references
References 29 publications
(52 reference statements)
3
207
0
3
Order By: Relevance
“…Mutations in GRIN2A have been found in a significant subset of patients with epilepsy-aphasia syndromes, comprising a phenotypic spectrum from atypical benign partial epilepsy to EEs with continuous spikes and waves during slow-wave sleep and LandauKleffner syndrome [Carvill et al, 2013b;Lemke et al, 2013;Lesca et al, 2013]. Furthermore, a few cases with severe early-onset EEs and severe ID as seen in the present case have been reported [Pierson et al, 2014]. The identified variant p.Asn614Ser is positioned directly at the tip of the re-entrant pore loop of GluN2A.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Mutations in GRIN2A have been found in a significant subset of patients with epilepsy-aphasia syndromes, comprising a phenotypic spectrum from atypical benign partial epilepsy to EEs with continuous spikes and waves during slow-wave sleep and LandauKleffner syndrome [Carvill et al, 2013b;Lemke et al, 2013;Lesca et al, 2013]. Furthermore, a few cases with severe early-onset EEs and severe ID as seen in the present case have been reported [Pierson et al, 2014]. The identified variant p.Asn614Ser is positioned directly at the tip of the re-entrant pore loop of GluN2A.…”
Section: Discussionmentioning
confidence: 81%
“…Variants of this domain have been shown to result in a significant loss of the Mg 2+ block resulting in a marked gain of channel function and severe neurodevelopmental delay [Endele et al, 2010]. Pierson et al [2014] recently reported that treatment with an NMDA receptor blocker, memantine, in a patient with intractable epilepsy and ID due to a GRIN2A gain-of-function mutation resulted in marked reduction of seizure frequency. However, the efficacy of memantine in patients with GRIN2A gain-of-function mutations remains to be confirmed in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, GRIN2A mutations were found in a subset of patients. GRIN2A is involved in neural development and cell adhesion (7)/ Memantine, an (NMDA) receptor antagonist has been reported to improve seizures and CSWS (8).…”
Section: Current Status Of Treatments For Children With Electrical Stmentioning
confidence: 99%
“…The authors predict that individuals with developmental and epileptic encephalopathy due to misTMD+Linker SNVs are prone to having an underlying gain of NMDAR function. These patients represent promising candidates for treatment with NMDAR blockers, such as memantine [Pierson et al, 2014]. Conversely, patients with SNVs leading to complete or partial loss of channel function (misATD+LBD or null variants) may potentially respond to positive allosteric modulators of the NMDAR [Zhu and Paoletti, 2015;Addis et al, 2017].…”
mentioning
confidence: 99%